Comorbidity of body dysmorphic disorder and bulimia nervosa (Archives of Clinical Psychiatry, 2012)
BACKGROUND: Body image dissatisfaction (BID) is a relevant psychopatological feature of eating disorders (ED), being one of the diagnostic criteria for both anorexia nervosa and bulimia nervosa (BN). Patients with ED may present BID not related to their weight, such as dissatisfaction with their skin, teeth and nose amongst others. The presence of BDI not related to weight raises the possibility of the presence of two diagnostics: ED and body dysmorphic disorder (BDD). CASE REPORT: In this article the case of a female with BN, who presented a significant distress with the appearance of her face, which compromised her social functioning in a larger extent than the ED, is reported. DISCUSSION: Although present diagnostic systems indicate that BDD should be diagnosed in the presence of BID (which can not be explained by other condition) some authors support that these symptoms are intrinsic characteristics of ED. This case report illustrates the need of a better understanding of these BID non-weight related complaints in eating disordered patients, and the occurrence of BDD as a comorbid condition in those individuals.